Ruptured rudimentary horn pregnancy of unicornuate uterus: a case report - Jena, Lopamudra; Satapathy, Rabi Narayan; Swain, Sujata; Mahapatra, Purna Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Unicornuate uterus with rudimentary horn occurs due to failure of complete development of one of the Mullerian ducts and incomplete fusion with the contralateral side. Pregnancy in the noncommunicating rudimentary horn is extremely rare and usually terminates in rupture during first or second trimester of pregnancy. Pregnancy occurs via transperitoneal migration of sperm or zygote. Variable thickness of rudimentary horn musculature, poor distensibility of myometrium lead to rupture. This complication is usually seen in 2nd trimester resulting in shock and haemoperitoneum. Diagnosis of rudimentary horn pregnancy is difficult and can be missed in ultrasound. It requires a high risk of suspicion. We report a case of G2A1 with pregnancy of 20 weeks gestation which was suspected as intraabdominal pregnancy on ultrasound and on laparotomy a live fetus of 19 weeks in intact gestational sac was found in ruptured left noncommunication horn of unicornuate uterus with haemoperitoneum. Timely laparotomy, excision of the horn and blood transfusion saved the patient.